PENGEMBANGAN LKPD BERBANTUAN GEOGEBRA BERBASIS BUDAYA BATAK TERHADAP KEMAMPUAN COMPUTATIONAL THINKING - Dalimunthe, Nabila Faiza; Israq Maharani; Nur Rahmi Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study used the Research and Development (R&D) technique with the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were seventh-grade students from SMP Negeri 29 Medan. The purpose of this project was to create a geogebra-assisted student worksheet (LKPD) based on Batak culture to help students enhance their computational thinking skills in the area of plane figures. Based on the validation results, the LKPD received an overall percentage of 88% from material specialists, media experts, and teachers, which is classified as very valid. The practicality analysis using teacher and student response questionnaires revealed ratings of 94% for teachers and 93% for students, both rated as very practical.The efficacy analysis was based on students' computational thinking test results, classical completeness, and student activity observation sheets. The geogebra-assisted Batak culture-based LKPD has been shown to be a viable medium for learning mathematics. The developed product not only improves students' understanding of plane figure concepts, but it also boosts learning motivation, promotes computational thinking skills, and instills local cultural values. As a result, this LKPD can be used as an innovative teaching material to help implement the Merdeka Curriculum.